Pemrograman Antarmuka Modem GSM dengan Pengendali Mikro AVR Menggunakan Bahasa C - Kartawiguna, Daniel (Bina Nusantara University, 2011)
Cell phones are now a cheap means of wide-ranged wireless communication. One feature widely used is the short message service (SMS). The cellular communication system is more appropriate for long-distanced applications than high speed data transfer. This study aims to develop a GSM modem interface with AVR microcontroller using C programming language. The tools controlled by the microcontroller system can gain more benefit if it is linked with GSM mobile communication system. The results of this study can be applied whether in a remote monitoring system, remote control system, or communication between the microcontroller via SMS. Many additional benefits can be obtained for the tools controlled by the microcontroller when connected to a GSM system.